Quad Axis Separation Framework for Bounding-Volume Hierarchies Construction - Sulaiman, Hamzah Asyrani (Journal of Computing, 2012)
The construction of Bounding-Volume Hierarchies (BVH) for Virtual Environment application has been varied from the rigid bodies application type to the deformable bodies application. Numerous technique and specific instruction has been given from several researchers in order to make sure that the BVH can suite their application without any restriction. In this paper, we explore the capability of BVH using a technique called Quad Axis Separation Technique (QAS) that could efficiently create full-blown hierarchical tree using approximation of separating axes theorem for Virtual Environment. A theoretical implementation is carried out with standard experimental that is also been used by researcher to test their BVH in the Virtual Environment. We also believed that QAS could provide fast and efficient hierarchical tree construction and also enhance the speed and accuracy of the collision detection technique.